Effect of lead and copper containing brine on steel materials for geothermal applications – A corrosion study. (March 2021) - Stoljarova, Anastasia; Regenspurg, Simona; Bäßler, Ralph; Mathiesen, Troels; Nielsen, Johan Braüner
Highlights: Understanding of the corrosion mechanism on alloys in geothermal conditions. Performance of the material selection to guarantee a secure and reliable operation of the geothermal facilities. Efficiency and reliability of geothermal systems and their competitiveness against conventional energy resources. The effect of copper and lead deposition on corrosion of carbon steel and stainless steel. Abstract: Geothermal brines often contain high amounts of lead and copper ions that can precipitate as native Cu 0 and Pb 0 as consequence of galvanic corrosion when brines react with carbon steel materials. This contribution evaluates which materials could overcome the problem of galvanic corrosion at geothermal environment. The behavior of these materials in water containing high chloride concentration (> 100 g/L NaCl) as well as various amounts of dissolved PbCl2 and/or CuCl2 was characterized by electrochemical and exposure measurements. Both methods reveal carbon steel suffers corrosion susceptibility, accompanied by Cu° and/or Pb° precipitation on the surface. Electrochemical measurements on stainless steels result in significant difference in corrosion and repassivation potentials (Ecorr = −189 mV, Erep =70 mV), indicating a good corrosion resistance.